2017
DOI: 10.1073/pnas.1704065114
|View full text |Cite
|
Sign up to set email alerts
|

Chemical probes to potently and selectively inhibit endocannabinoid cellular reuptake

Abstract: The extracellular effects of the endocannabinoids anandamide and 2-arachidonoyl glycerol are terminated by enzymatic hydrolysis after crossing cellular membranes by facilitated diffusion. The lack of potent and selective inhibitors for endocannabinoid transport has prevented the molecular characterization of this process, thus hindering its biochemical investigation and pharmacological exploitation. Here, we report the design, chemical synthesis, and biological profiling of natural product-derived -substituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
163
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 85 publications
(172 citation statements)
references
References 51 publications
6
163
2
1
Order By: Relevance
“…39, 40 Finally the functional activity of the new compounds was determined by SRE assay using HEK293 cells transfected with CB1R. 41 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…39, 40 Finally the functional activity of the new compounds was determined by SRE assay using HEK293 cells transfected with CB1R. 41 …”
Section: Methodsmentioning
confidence: 99%
“…39,40 Briefly, FAAH and MAGL activity assays were performed using U937 cell homogenate (100 μg) which were diluted in 200 μL of Tris–HCl 10 mM, EDTA 1 mM, pH 8 containing 0.1% fatty acid-free BSA. Compounds were added at the screening concentration of 10 μM and incubated for 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of directly modulating the pharmacophore, a linker can be used, and the modified drug is challenged to undergo direct attachment at the pharmacophore through the CF 3 ‐diazirine group (Figure d). Chicca et al . synthesized probe 8 by replacing a methyl ether with an amide‐derived TPD and showed that the use of a linker can maintain efficacy.…”
Section: Applications Of Affinity Labelingmentioning
confidence: 99%
“…Instead of directly modulating the pharmacophore,al inker can be used, and the modified drug is challenged to undergo direct attachment at the pharmacophore through the CF 3 -diazirine group (Figure 1d). Chicca et al [10] synthesized probe 8 by replacing amethyl ether with an amide-derived TPD and showed that the use of al inker can maintain efficacy.The design of TPD-based probes needs to be evaluated on ac ase-by-case basis.T PDs with aromatic rings may be analogues for pharmacophores that also contain aromatic rings to which aC F 3 -diazirine group can be attached. Even when the CF 3 -diazirine group is directly incorporated, structure-reactivity relationships (SARs) should be carefully considered.…”
Section: -Trifluoromethyl-3-phenyldiazirine Derivativesmentioning
confidence: 99%
“…Anstatt den Pharmakophor direkt zu modifizieren, kann ein Linker verwendet werden, wenn ein modifizierter Wirkstoff dazu gezwungen wird, direkt mittels der CF 3 -Diazirin-Funktion an den Pharmakophor zu binden (Abbildung 1d). Chicca und Mitarbeiter synthetisierten Reagenz 8, [10] in dem eine Methyletherfunktion durch ein Amid-derivatisiertes TPD ersetzt wurde,w obei die Effizienz trotz des Linkers erhalten blieb.A lles in allem muss das Design eines TPD-basierten Reagenzes von Fall zu Fall evaluiert werden. TPDs mit aromatischen Ringen kçnnen als Analoga für Pharmakophore wirken, in denen eine CF 3 -Diazirin-Gruppe an das Aren gebunden wird.…”
Section: Anwendungen Der Affinitätsmarkierungunclassified